How to have a good day : harnessing the power of behavioral science to transform our working lives - Webb, Caroline, 1971- (Crown Business, 2016)
"In How to Have a Good Day, Caroline Webb, business consultant and former partner at powerhouse McKinsey and Co., brings together the findings on behavioral economics and neuroscience--subjects that have led to dozens of bestselling books over the last decade--to show us how we can use these revolutionary new findings to improve how we work. Organized around seven factors that determine whether we have a good day at work, Webb offers us specific tools that we can use based on what we now know about how our brains work, and she shows us how we can incorporate them into our conversations, meetings, and projects in a way that will increase productivity, confidence, and enjoyment. Filled with stories of people who have used the insights Webb reveals to improve the quality of their decision-making and work lives, and drawing on cutting-edge ideas from the latest research in neuroscience and psychology, How to Have a Good Day is the book people wanted to read when they finished Blink and Thinking Fast and Slow, and were looking for practical ways to apply the new insights they had learned to their own lives and careers. From the time we wake up, Webb reveals the tools and practices that will help us to set our direction and priorities, organize our time, do our best work, adapt to uncertainty, make better decisions, improve our conversations, unleash productivity, and sustain our energy. In essence, she offers us a Good Day playbook, showing us how to sharpen our minds and increase our confidence so that we make sustained progress, resist our tendency to procrastinate, resolve conflict, and maintain control of our day and bounce back from the inevitable setbacks"--